2014
DOI: 10.1080/00224545.2014.959884
|View full text |Cite
|
Sign up to set email alerts
|

The Campbell Paradigm as a Conceptual Alternative to the Expectation of Hypocrisy in Contemporary Attitude Research

Abstract: Hypocrisy-professing a general attitude without implementing corresponding attitude-relevant behavior-is, according to Ajzen and Fishbein (2005), commonly found in attitude research that aims to explain individual behavior. We conducted two studies that adopted the Campbell paradigm, an alternative to the traditional understanding of attitudes. In a laboratory experiment, we found that specific attitude-relevant cooperation in a social dilemma was a function of people's pre-existing general environmental attit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 35 publications
3
35
0
2
Order By: Relevance
“…Specifically-and in line with ample previous evidence of green defaults effectively facilitating people's environmentally friendly behavior (e.g., Pichert & Katsikopoulos, 2008)-we expected a main effect of the default, such that green defaults result in more green choices (Hypothesis 2). Building on previous findings of environmental attitude controlling both environmentally friendly behavior generally (e.g., Kaiser & Byrka, 2015), as well as sustainable consumer choices specifically (e.g., Tanner & Wölfing Kast, 2003), we also expected a main effect of environmental attitude, with higher attitude levels resulting in more green choices…”
Section: Hypothesesmentioning
confidence: 92%
See 1 more Smart Citation
“…Specifically-and in line with ample previous evidence of green defaults effectively facilitating people's environmentally friendly behavior (e.g., Pichert & Katsikopoulos, 2008)-we expected a main effect of the default, such that green defaults result in more green choices (Hypothesis 2). Building on previous findings of environmental attitude controlling both environmentally friendly behavior generally (e.g., Kaiser & Byrka, 2015), as well as sustainable consumer choices specifically (e.g., Tanner & Wölfing Kast, 2003), we also expected a main effect of environmental attitude, with higher attitude levels resulting in more green choices…”
Section: Hypothesesmentioning
confidence: 92%
“…Likewise—and despite recurrent claims of an attitude‐behavior gap (see e.g., Kollmuss & Agyeman, )—previous research demonstrates the predictive power of environmental attitude, at least when people's attitude is assessed with validated and reliable measures (Kaiser & Byrka, ). Notwithstanding the importance of other personal factors such as goals, knowledge, and values (e.g., Lindenberg & Steg, ; see Gifford & Nilsson, , for an overview), a range of studies have shown that environmental attitude predicts pro‐environmental behavior generally (e.g., Kaiser, Byrka, & Hartig, ) and environmentally friendly consumer behavior specifically (e.g., Roberts & Bacon, ; Tanner & Wölfing Kast, ).…”
Section: Introductionmentioning
confidence: 99%
“…Attitude towards a given object is only person-dependent and reflects itself through a set of behaviours transitively ordered according to the level of difficulty (cost) to perform them: in practice, attitudes are measured by means of what people do, not of what they say. With such a Campbellian measure of attitudes, as explained by Kaiser and Byrka [125] (p. 26), "there is no room for hypocrisy": people put their general attitudes into specific attitude-relevant practices and differences in people's general attitudes can be derived from their attitude-relevant behaviour. Indeed, we can consider that a bike commuter shows a higher behavioural disposition to cycling than someone who states that (s)he is feeling good, feels loved and is encouraged by peers to use the bike.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al, (2002) also contends that using attitude-behaviour as a justification for psychological and marketing theorizing ought to be discarded. From Campbell's perspective, the only causative factor to attitude-behaviour gap is the differential difficulties associated with such behaviour and hence regard it as a methodological rather than a theoretical challenge (Kaiser and Byrka, 2015).…”
Section: Campbell's Paradigm and Sustainable Purchase Behaviourmentioning
confidence: 99%
“…In our opinion, this represents a comprehensive research on sustainable food purchase behaviour because it eliminates social desirability bias (Drichoutis et al, 2016) and hypocrisy (Kaiser and Byrka, 2015). Hence, the first objective of the study is to draw on Campbell's paradigm to develop a sustainable product purchase behaviour model by conceptualising and measuring behavioural difficulties in terms of Past Purchase, Premium Pricing, and Product Availability and Product Variety barriers.…”
mentioning
confidence: 99%